Sox8 is essential for M cell maturation to accelerate IgA response at the early stage after weaning in mice - Kimura, Shunsuke (J Exp Med, 2019)
Microfold (M) cells residing in the follicle-associated epithelium (FAE) of the gut-associated lymphoid tissue are specialized for antigen uptake to initiate mucosal immune responses. The molecular machinery and biological significance of M cell differentiation, however, remain to be fully elucidated. Here, we demonstrate that Sox8, a member of the SRY-related HMG box transcription factor family, is specifically expressed by M cells in the intestinal epithelium. The expression of Sox8 requires activation of RANKL-RelB signaling. Chromatin immunoprecipitation and luciferase assays revealed that Sox8 directly binds the promoter region of Gp2 to increase Gp2 expression, which is the hallmark of functionally mature M cells. Furthermore, genetic deletion of Sox8 causes a marked decrease in the number of mature M cells, resulting in reduced antigen uptake in Peyer’s patches. Consequently, juvenile Sox8-deficient mice showed attenuated germinal center reactions and antigen-specific IgA responses. These findings indicate that Sox8 plays an essential role in the development of M cells to establish mucosal immune responses.